The effect of co-chemotherapy of ethyl acetate fraction of Long jack roots (Eurycoma longifolia jack) on interleukin-6 expression of 7,12- dimethylbenz anthrasen breast carcinoma model - Siti Salma Yusuf; Laela Hayu Nurani; Sitarina Widyarini (Faculty of Medicine, Universitas Islam Indonesia, 2018)
Background: Carcinogenic compound can cause cancer, one of which is 7,12- Dimethylbenz anthrasen (DMBA). Therapy used is chemotherapy using doxorubicin. However, doxorubicin can cause side effects and not specific enough, so it can also impair normal cells and cause resistance, so Long jack roots are needed as co- chemotherapy agent.Objective: To assess the effect of giving co-chemotherapy ethyl acetate fraction of Long jack roots and doxorubicin on the development of breast cancer through inhibition interleukin-6 expression.Methods: A total of 35 female rats SD strain were divided into 5 intervention group, each group contained 7 rats, namely Group 1 (baseline given feed and water), Group 2 (DMBA 20 mg / kg given 2x a week for 5 weeks), Group 3 (DMBA 20mg / kg + Long jack roots Ethyl acetate fraction 100 mg / kg), Group 4 (DMBA 20 mg / kg + Doxorubicin 1,17mg / kg), Group 5 (DMBA 20 mg / kg + Long jack roots ethyl acetate fraction 100 mg / kg + Doxorubicin 1,17mg / kg), then on the 16th week, surgery was done to remove animal’s mammae and organs and to conduct immunohistochemistry test with anti interleukin-6. Results: Interleukin-6 expression test result% with the average value of group I, II, III, IV and V respectively, 6.56 ± 3.50%; 47.21 ± 9.48%; 20.83 ± 10.40%; 49.39 ± 9.87% and 58.37 ± 17.32%.Conclusion: The administration of co-chemotherapy ethyl acetate fraction of longjack roots (Eurycoma longifolia Jack) and doxorubicin is effective inlowering aromatase expression, however not effective in reducing IL-6 expression compared to single regiment doxorubicin in DMBA-induced rat models.